Intussusception in cat: case report - Neto, J. Bartolomei; Vasconcelos, A. L.; Ferreira, A. S.; Santi, F. S. C.; Lazarotto, W. V.; Novais, A. A. (Scientific Electronic Archives, 2020)
Intestinal obstruction is among the most common causes requiring surgical intervention in the small animal clinic. The more proximal and complete the obstruction, the more acute and intense the signs will be and the greater the likelihood of dehydration, electrolyte imbalance and even death. Among the causes of intestinal obstruction, intussusception may be the one with the highest prevalence. It is usually of idiopathic origin, has no racial and sexual predisposition, and its highest incidence is found in young animals. Predisposing factors are often associated, such as parasitism, gastroenteritis and foreign bodies where the treatment is usually surgical. In the present study we describe a case of a feline, female, one year and two months old with intestinal obstruction, presenting with four days’ emesis, hypophagia, dehydration and apathy. This work aims to contribute to the knowledge and alert to a rapid differential diagnosis of intestinal obstructions which is a frequent and important disorder in the small animal clinic and is not always diagnosed in time.